Boys among men : how the prep-to-pro generation redefined the NBA and sparked a basketball revolution - Abrams, Jonathan P. D., 1984- (2016)
"When Kevin Garnett shocked the world by announcing that he would not be attending college--as young basketball prodigies were expected to do--but instead enter the 1995 NBA draft directly from high school, he blazed a trail for a generation of teenage basketball players to head straight for the pros. That trend would continue until the NBA instituted an age limit in 2005, requiring all players to attend college or another developmental program for at least one year ... [This book] goes behind the scenes and draws on hundreds of first-hand interviews to paint ... portraits of the most pivotal figures and events during this time"--Amazon.com
Keywords: National Basketball Association; Basketball draft; Basketball players -- Recruiting -- United States